Rancang Bangun Sistem Informasi Pencatatan Transaksi Keuangan Berbasis Website di PT. Gilang Arthajaya Abadi - Meiliana Meiliana; Tri Nur Arifin (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to design and implement a website-based financial information system to support the digital transformation process at PT. Gilang Arthajaya Abadi. The background of this study stems from the problem of managing financial transactions that are still carried out manually without the support of a computerized system, resulting in obstacles in data retrieval, the risk of information loss, and difficulties in recapitulating transaction data. To overcome these problems, this study uses the waterfall system development method which has a structured and sequential approach, including the stages of needs analysis, design, implementation, testing, and maintenance. This method was chosen because the system requirements have been clearly defined from the beginning, thus minimizing the possibility of changes during the development process. The system design was carried out using the Unified Modeling Language (UML) to visualize the needs and process flow, while the technologies used include PHP as a programming language, MySQL as a database, and the Laravel framework to support the development of an efficient, structured, and easily developed system in the future. The resulting system is able to facilitate the recording of financial transactions in a more structured manner, increase data accuracy, minimize the risk of information loss due to human error, and accelerate the process of searching and creating financial reports. Test results indicate that all developed features, such as transaction recording, data management, and report generation, function well according to user needs. Implementation of this system is expected to improve the company's operational efficiency, strengthen internal controls, and serve as the first step in building an integrated digital ecosystem at PT. Gilang Arthajaya Abadi. This research also opens up opportunities for further development, such as integration with online payment systems and big data-based financial analytics to support the company's strategic decision-making.